Hemostatic Risk Factors for Atherothrombotic Disease: An Epidemiologic View - Folsom, Aaron R. (Thrombosis and Haemostasis, 2001)
A number of prospective epidemiologic studies have now tested the hypothesis that plasma measures of hemostatic factors measured in initially healthy subjects may predict the future onset of atherothrombotic events. Epidemiologic evidence is very strong that plasma fibrinogen is a risk marker, if not a causal factor, for atherothrombotic events. Evidence is mixed on whether factor VII, factor VIII, von Willebrand factor, or other coagulation markers predict incident atherothrombosis. D-dimer is emerging as a strong risk marker, as are several fibrinolytic markers such as tPA antigen – but not PAI-1. Despite suggestive studies, no genetic polymorphism influencing hemostatic factor levels has emerged as a consistent and strong risk factor for atherothrombosis. Thus, prospective epidemiologic studies have identified several potential hemostatic markers of atherothrombosis risk, but their causal role and clinical utility in risk prediction remain incompletely established.
Keywords: Atherosclerosis; coronary disease; fibrinogen; fibrinolysis; coagulation factors